Molecular tools for characterisation of Theileria parva - Morzaria, S.P.; Bishop, Richard P.; Nene, Vishvanath M.; Skilton, Robert A.; Geysen, D.; Mbogo, S. (Monduzzi Editore S.p.A., 1998)
In order to discriminate different bovine Theileria species and to characterise genetic diversity in the pathogenic T. parva, a range of diagnostic and molecular tools have been developed. The diagnostic tools are based on recombinant antigens used in ELISAs and the molecular tools are based on parasite-specific repetitive sequences, random DNAs, antigen genes, mitochondrial DNA and small subunit ribosomal RNA genes. Using mainly southern blotting technique and PCR analysis, a comprehensive characterisation of the T. parva vaccine and field stocks has been obtained. These tools are increasingly being used in quality control of vaccines. Characterisation of parasite populations and epidemiology of theileriosis in conjunction with the deployment of live T. parva vaccines.